2017
DOI: 10.4236/ojss.2017.710019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Management Practices on Water Extractable Organic Carbon and Nitrogen from 12-Year Poultry Litter Amended Soils

Abstract: Water extractable organic carbon (WEOC) and nitrogen (WEON) are two key parameters of soil water extractable organic matter (WEOM). Proper management of manure application rate in combination with tillage and cropping management could maintain appropriate WEOC and WEON concentrations in soils while decreasing the risk of their runoff from cropland and pastures. The objective of this research was to determine the effect of poultry litter (PL) application on WEOC and WEON in soils under different crops, tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
1
5
3
Order By: Relevance
“…Like SUVA 254 values, the E2/E3 of native grassland did not change significantly with depth, with a narrow E2/E3 range of 1.47-2.00 (Figure 4b; Table 1). These values are slightly lower than those reported by He et al (2017) (3.15-3.57) for native T A B L E 5 Correlation coefficients among quality and quantity parameters measured for water-extractable organic matter, year sampled (1977,2013), crop type up to 1977 (continuous wheat, wheat-fallow), tillage (disk plow, stubble mulch, delayed stubble mulch), and depth sampled (0-80, 80-150, 150-230, and 230-300 6, 4.3, 5.8, and 14.4 at D1, D2, D3, and D4, respectively. Despite a trend for higher E2/E3 values with CW-DP, CW-ST, and WF-DST below the plow layer (D4) in 1977, there was no statistical significance (Table 4).…”
Section: Ultraviolet-visible Spectral Characteristics Of Water-extrac...contrasting
confidence: 67%
See 1 more Smart Citation
“…Like SUVA 254 values, the E2/E3 of native grassland did not change significantly with depth, with a narrow E2/E3 range of 1.47-2.00 (Figure 4b; Table 1). These values are slightly lower than those reported by He et al (2017) (3.15-3.57) for native T A B L E 5 Correlation coefficients among quality and quantity parameters measured for water-extractable organic matter, year sampled (1977,2013), crop type up to 1977 (continuous wheat, wheat-fallow), tillage (disk plow, stubble mulch, delayed stubble mulch), and depth sampled (0-80, 80-150, 150-230, and 230-300 6, 4.3, 5.8, and 14.4 at D1, D2, D3, and D4, respectively. Despite a trend for higher E2/E3 values with CW-DP, CW-ST, and WF-DST below the plow layer (D4) in 1977, there was no statistical significance (Table 4).…”
Section: Ultraviolet-visible Spectral Characteristics Of Water-extrac...contrasting
confidence: 67%
“…The importance of WEOM on soil fertility has been recognized within the past few decades (Haynes, 2005). Soil WEOM typically comprises only a small portion (<3%) of total soil organic matter (SOM; Zhao et al, 2013), but is dynamic, mobile, and more sensitive to climate and land management practices than SOM (Bremer et al, 1994;He et al, 2016He et al, , 2017. Chaudhary et al (2017), Ohno et al (2009), and…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported both accumulation and redistribution of EOC or WEOC in soils (Gonet and Debska 2006), whereas others found evidence of accumulation but not redistribution of EOC/WEOC or DOC to depth (Angers et al 2006;Long et al 2015;He et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a lysimeter study in China, Long et al (2015) reported greater DOC in the surface soil for liquid pig manure compared to unamended control, but not at deeper depths to 90 cm. He et al (2017) found that poultry litter application to five cultivated soils in Texas increased WEOC in the surface (0-15 cm) soil compared to the unamended control; but they did not sample deeper depths.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation